1985
DOI: 10.1042/cs0680049
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Parasympathetic Activity of the Angiotensin Converting Enzyme Inhibitor, Captopril, in Normotensive Man

Abstract: Captopril (50 mg orally) produced a significant fall in systolic and diastolic blood pressure in six normotensive sodium replete subjects, without a rise in heart rate. On captopril, there was no change in the expected normal increase in heart rate on standing. Supine plasma noradrenaline was not reduced by captopril and normal postural increases were maintained. Atropine (0.04 mg/kg i.v.) reduced the difference in blood pressure change between captopril and placebo. Facial immersion in water produced a bradyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
1
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 0 publications
5
33
1
1
Order By: Relevance
“…The absence of reflex tachycardia with blood pressure reduction after ACE inhibitors appears, in part, to be related to an enhancement of cardiac parasympathetic tone (Sturani et al, 1982;Campbell et al, 1985;Ajayi et al, 1985a) following the withdrawal of the vagolytic actions of angiotensin II (Ajayi et al, 1985b).…”
Section: Autonomic Function Testsmentioning
confidence: 99%
“…The absence of reflex tachycardia with blood pressure reduction after ACE inhibitors appears, in part, to be related to an enhancement of cardiac parasympathetic tone (Sturani et al, 1982;Campbell et al, 1985;Ajayi et al, 1985a) following the withdrawal of the vagolytic actions of angiotensin II (Ajayi et al, 1985b).…”
Section: Autonomic Function Testsmentioning
confidence: 99%
“…The absence of reflex cardioacceleration, even after acute dosing, suggests that ACE inhibitors exert some specific influence on, for example, autonomic reflex mechanisms or baroreflex integrity. There is no evidence to suggest that ACE inhibition significantly modifies either sympathetic tone or baroreflex function in man (Millar et al, 1982) but enhancement of-cardiac parasympathetic activity has been reported with captopril, enalapril and lisinopril (Sturani et al, 1982;Campbell et al, 1985;Ajayi et al, 1985a, b …”
Section: Introductionmentioning
confidence: 99%
“…The release of vagal pathways from angiotensin II mediated inhibition, both centrally and peripherally may well enhance cardiac parasympathetic tone, thus blunting the reflex tachycardia (Sturani et al, 1982;Ajayi et al, 1985a,b;Campbell et al, 1985).…”
mentioning
confidence: 99%
“…Their focus was mainly on baroreceptor reflexes, hence their article somehow obscures other possible explanations for the absence of reflex cardioacceleration including (1) a central sympatho-inhibitory action, (2) removal of the peripheral angiotensin II (All) mediated presynaptic facilitation of noradrenaline release, (3) unchanged arterial wall tangential tension during ACE inhibition, (4) selective venodilatation or (5) parasympathetic activation. The relative merits of these propositions have been examined previously (Sturani etal., 1982;Ajayi etal., 1985 a,b;Campbell et al, 1985;Levenson et al, 1985).…”
mentioning
confidence: 99%